New Elements of Digital Transformation - Bonnet, Didier (MIT Sloan Management Review, 2020)
Recent advances in digital technology and the shift to digital activity accelerated by COVID-19 make digital mastery more essential than ever. In this article, Didier Bonnet of IMD and George Westerman of MIT's Sloan School reappraise the elements of digital capability and identify where the opportunities lie for gaining competitive advantage in customer experience, internal operations, employee experience, and business model innovation, as well as the digital platforms needed to access them.